The Role of Agglomeration Economies on Technical Efficiency of Manufacturing Industries in East Java - Restikasari, Wenny; Dewita Ike , Pramudiya; Bella Sinta , Nuriya (Universitas Gorontalo, 2026)
This study aims to determine the effect of agglomeration economies on technical inefficiency at the firm level of the manufacturing industry in East Java. The data establish from an annual survey of medium and large manufacturing conducted by Statistical Indonesia covering 2010-204. The Stochastic Frontier Analysis method is used to determine the economic agglomeration of technical inefficiency. The results show that specialization has positive influence on technical inefficiency, while Diversion and Firm Size have a negative influence on technical inefficiency of manufacturing industry firms in East Java Province. Although competition does not influence technical inefficiency. Therefore, the government should consider the externalities of agglomeration including specialization, diversity, and competition, that provide significant advantages to manufacturing companies in East Java. Nevertheless, while these agglomeration benefits contribute to economic growth, they often do not correspond to the actual environmental conditions.